The jam session and jazz studies - Pinheiro, Ricardo (2020)
This paper examines relevant works on jam session, focusing on how this performative practice has been approached in jazz literature. Starting from bibliographical research and the fieldwork the author analyzes to what extent these works reflect poor and decontextualized perspectives on a performative practice that is crucial for the development of the creative process, learning and construction of professional musicians' networks. The existing studies on the jam session are insufficient for obtaining considerable information about this practice in its musical, social and cultural settings, namely in terms of its functioning and role in the context of the jazz scene. The musicians' discourse is often neglected in most works on this topic.